Legal system of digital contracts - Radha, Asst.Prof.D. Avan Abdul Aziz Radha; Qadir, Tebin Kamal Arief Qadir (Sulaimani Journal for Humanities, 2025)
Digital contracts are those contracts that are concluded through block chain technology, which is considered one of the modern contracts that arose in light of the advanced technology for conducting financial transactions without the need for human intervention. These digital contracts are concluded and implemented by entering the terms and conditions of the contract into an electronic program that automatically implements all the terms of the contract once their validity is verified. The electronic program documents those contracts and digital transactions and records them in a chain that is visible to all users and cannot be Making any forgery or modification therein, and thus the contracting parties find themselves in a few minutes having completed their contractual transaction with the highest levels of speed, reliability, and safety, and at the lowest cost. Based on this, the agreement of the two wills in the smart contract, its procedures cannot be stopped once the two wills meet on them, which make these contracts less costly because they do not need the third element such as a lawyer, mediator, broker or notary. Therefore, the research aimed to present the concept of the digital contract and determine the period of application of the concept of the contract in the legal sense to transactions that take place via blockchain technology and to identify its characteristics and shortcomings.
Keywords: Digital contract; blockchain; software; self executing contracts; cryptocurrencies; encryption; trust